1987
DOI: 10.3354/meps035119
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and dissolved lipid classes in cultures of Phaeodactylum tricornutum grown in cage culture turbidostats with a range of nitrogen supply rates

Abstract: Production of intracellular and extracellular algal hpid classes was examlned over a range of rates of supply of Inorganic nitrogen The marine dlatom Phaeodactylum tncornutum was studied using 2 new techniques Cage culture turb~dostdts wt rl used for growing the phytoplankton These are continuous cultunng systems which provldc-a h~g h l y controlled algal environment The Chromarod-Iatroscan TLC/FID system was used for llpid class separat~on and quantification This permitted the resoluhon and detechon of as man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
4
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 14 publications
8
73
4
1
Order By: Relevance
“…ST consistently showed a sharp increase on the day of the chlorophyll maximum. This result, coupled with the linear relation between sterols and growth rate in turbidostat cultures (Parrish & Wangersky 1987), suggests that where chlorophyll a values are high, enhanced particulate sterol levels can also be used as an indicator of healthy, actively dividing cells. The second ST peak observed in 1982 (Fig.…”
Section: Spring Bloom: General Observationsmentioning
confidence: 89%
See 3 more Smart Citations
“…ST consistently showed a sharp increase on the day of the chlorophyll maximum. This result, coupled with the linear relation between sterols and growth rate in turbidostat cultures (Parrish & Wangersky 1987), suggests that where chlorophyll a values are high, enhanced particulate sterol levels can also be used as an indicator of healthy, actively dividing cells. The second ST peak observed in 1982 (Fig.…”
Section: Spring Bloom: General Observationsmentioning
confidence: 89%
“…By growing a single species of phytoplankton in a highly controlled environment it s h o d d be possible to examine the rate of production of intracellular and extracellular lipids as a function of the rate of supply of nutrients, provided all other variables are kept constant. This can be done with cage culture turbidostats (Parrish & Wangersky 1987), which provide a means of maintaining a constant population density while preventing the accumulation of exudation products in the medium. Using this culture technique it was found that the rate of production of intracellular triglycendes in the diatom Phaeodactylum tricornutum increased with increasing nitrogen stress, while the rate of production of total lipids actually decreased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pelagic ecosystems, the quantity and quality of particulate material is highly variable both temporally and spatially (Jeffries 1970, Kattner et al 1983, Parrish 1987, Frazer et al 1989, Mayzaud et al 1989, Pond et al 1993) and this variability in the nutritional environment is thought to be a significant factor controlling secondary production.…”
Section: Introductionmentioning
confidence: 99%